Adopsi dan Dampak Teknologi Informasi Dalam Mendukung Kinerja Berbasis Teknologi Informasi (Studi Kasus Biro Hukum Setda Provinsi Sulawesi Tengah) - Melisa Prisilia Lembonunu; Andeka Rocky Tanaamah (Jurnal Teknik Informatika dan Sistem Informasi, 2018)
The presence of the information technology (IT) has important roles for the Law Bureau on the dissemination of information and law products in Central Sulawesi. As is the urgency for the law information that leads to enhance the quality of public service, the presence of Law Documentation Network Department (JDIH) in Central Sulawesi was expected to be a responsible department in order to deploy the law information with the implementation of information technology by website. This research uses qualitative method on data retrieval, that is done by interview to several staffs in Law Bureau, Central Sulawesi. The result of this research is that there are several factors that urge the adoption of IT on Law Bureau, that is: (a) there is urgency of people against the law Bureau, (b) the adoption of information technology was an effort of the Law Bureau to enhance the service quality, (c) the time effectiveness of law information dissemination. Other than that, this research also found the fact that the quality of human resource in the Law Bureau is not so espouse, therefore IT impacts the JDIH website management. There are several positive impacts as well for the vertical agency that connected with the Law Bureau and society in Central Sulawesi.